HETEROLOGOUS EXTRACELLULAR EXPRESSION OF BACTERIAL PHYTASE (AppA) IN Pichia pastoris AND ITS BIOCHEMICAL CHARACTERIZATION - Kirillov , S.; Silayev , D.; Abeldenov , S.; Khassenov, B. (Eurasian Journal of Applied Biotechnology, 2016)
Phytase, used as an animal feed additive, catalysesphytic acid hydrolysis with sequential release of phosphate and reduces feeding costs. In this work, we amplified the Escherichia coli acid phosphatase gene appA and inserted it into an expression vector pPICZαA. appA was under the control of inducible promoter of alcohol oxidase AOX1 with an α-factor signal peptide, which provides secretory protein expression. The recombinant plasmid was purified and lineariszed with the restriction enzyme PmeI, followed byits transformation into the host strain Pichia pastoris GS115,using electroporation. The transformed P.pastoris GS115 grew well on YPDS containing 100 µg/mL zeocin. PCR results confirmed the integration of appA into the genome of P. pastoris. SDS-PAGE analysis revealed that phytase was over expressed and secreted into the culture supernatant. The maximal extracellular activity and optimum temperature of phytase was reported to be 1510 U/mL and 50°C, respectively. Phytase was active at pH 2.0-7.0, with optimum activity at pH 5.0. The recombinant protein was thermostable and retained 80% of its activity after incubation at 60°C for 10 min. Protein glycosylation was confirmed with endoglycosidase H. The recombinant yeast strain P. pastoris GS115 pPICZαA/AppA exhibits potential industrial applications.